Hubungan Fungsi Kognitif dengan Perawatan Diri: Aktivitas Sehari-hari pada Lansia Hipertensi di UPT PSTW Jember : Relationship between Cognitive Function and Self-Care: Daily Activities in Hypertensive Elderly at UPT PSTW Jember - Annisah Dwi Intan Firdausi Nuzula; Latifa Aini Susumaningrum; Hanny Rasni; Tantut Susanto; Muqodimatul Masruro (NERS Jurnal Keperawatan, 2021)
Hypertension among elderly can decrease the status of cognitive function, that affected for self-care activity: daily activities for the long term. The aimed of this study was to analyze the relationship between cognitive function and self-care: daily activities in elderly hypertension in UPT PSTW Jember. A cross-sectional study was used among 61 elderlies using total sampling. A self–administred questionnaire was used to identify sociodemography of elderlies, while Mini Mental State Examination (MMSE) was used to measure cognitive function, and the Index Katz was used to measure elderly daily self-care. The relationship between cognitive function and self-care: daily activities in elderly hypertension using Chi-square test. The results showed that most of the elderly were a normal cognitive function status (37.7%) and independence doing daily activities (47.5%). There was significant relationship between cognitive function and self-care: daily activities in elderly hypertension (p-value 0.018, X2 8.005). The conclusion of this study that cognitive function is related to self-care: daily activities in elderly hypertension. Therefore, elderly should maintain good cognitive function in order to be independent in performing self-care: daily activities.